Food behaviours of Italian consumers at risk of poverty. Issue 11 (2nd November 2015) - Ruggeri, Arianna; Arvola, Anne; Samoggia, Antonella; Hendrixson, Vaiva; Griffith, ChristopherJ.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose At a European level, Italy experiences one of the highest percentages of population at risk of poverty (AROP). However, studies on this consumer segment are scarce. The paper aims at investigating the food behaviours of Italian female consumers, distinguishing similarities and differences due to age and level of income. Design/methodology/approach The investigation adopted an inductive approach in order to analyse and confirm the determinants of food behaviours. Data were collected through four focus groups. Data elaboration included content analyses with term frequency–inverse document frequency index and multidimensional scaling technique. Findings The food behaviours of Italian female consumers are based on a common set of semantic categories and theoretical dimensions that are coherent with those applied by previous studies. The age of consumers impacts the relevance attributed to the categories and income contributes to the explanation of the conceptual relations among the categories that determine food behaviours. The approach to food of younger and mature consumers AROP is strongly driven by constraints such as price and time. The study did not confirm a link between a poor health attitude and low socio-economic status. Research limitations/implications The outcomes achieved can be strengthened by quantitative analyses to characterise the relations occurring among the factors and dimensions that influence the food behaviours of consumers AROP. Originality/value The study increases knowledge about Italian female consumers and provides an initial contribution to the analysis of the food behaviour of the population AROP.